Formes brèves avec figures de peintres - Vignes, Sylvie (Romanica Silesiana)
<!–EndFragment–>If literature never could ignore visual arts, its « substantial allies » as René Char calls them, literary modernity wovens particularly close, varied and complex bonds with all kinds of picture. In this way, « couples » are often formed, for example, by a novelist and a painter (Pierre Michon and Van Gogh, François Bon and Edward Hopper, Philippe Delerm and Tiepolo…). The « substantial ally » inspires then a tale, or a sort of a literary inquiry, while other ones prefer a more brief form for this pictural theme. Now, specialists agree to emphasize that it’s a short story, Balzac’s Chef-d’œuvre inconnu, which, in France initiated, in 1831, this fertile connection between narrative fictions and visual arts. We attempted to surround this illustrious ancestor’s salient features in order to compare with it an other brief narrative fiction : Comment Wang-fô fut sauvé, a fairy tale written a century later by Marguerite Yourcenar. Key words: Balzac, Marguerite Yourcenar, narrative fictions, brief forms, shorts stories, fairy tales, visual arts.